2017
DOI: 10.1002/tox.22387
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin‐1 and microRNA‐1 expression in response to multiwalled carbon nanotubes in alveolar epithelial cells

Abstract: Thrombospondin-1 (TSP-1) is a glycoprotein that plays a role in extracellular matrix (ECM) remodeling. Previously, we have shown that multi-walled carbon nanotubes (MWCNT) regulate ECM components TGFβ and its target Col3A1 in alveolar epithelial cells. In the present study, we investigated the effect of MWCNT on TSP-1 and microRNA-1 (miR-1) in the regulation of TGFβ in ECM remodeling using alveolar epithelial A549 cells. A549 cells were treated with MWCNT (20 or 50 µg/ml) for 6 or 24 h and the expression of TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…MiRNAs (miR122/206/130/210) in the blood were significantly up- or down-regulated in mice with pathological alteration in the lung after methylcholanthrene administration followed by MWCNT inhalation [ 34 ]. MiR1 was suppressed by MWCNT after 6 or 24 h of treatment regardless of the dosage in alveolar epithelial A549 cells, and exogenous administration of miR1 induced cell morphology changes including cell clustering, whereas inhibition of miR1 induced less cell to cell contact, cell rounding, and cellular projections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs (miR122/206/130/210) in the blood were significantly up- or down-regulated in mice with pathological alteration in the lung after methylcholanthrene administration followed by MWCNT inhalation [ 34 ]. MiR1 was suppressed by MWCNT after 6 or 24 h of treatment regardless of the dosage in alveolar epithelial A549 cells, and exogenous administration of miR1 induced cell morphology changes including cell clustering, whereas inhibition of miR1 induced less cell to cell contact, cell rounding, and cellular projections [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TGF β in complex with TSP-1 is biologically active and favors TGF β binding to cell receptors [ 101 ]. Platelets, endothelial cells, smooth muscle cells, neutrophils, monocytes, macrophages, alveolar macrophages, fibroblasts, and epithelial cells all produce TSP-1 [ 102 106 ]. TSP-1 regulates multiples cellular processes such as cell migration, cell adhesion, cell proliferation, apoptosis, coagulation, wound repair, and fibrosis [ 107 , 108 ].…”
Section: Mechanisms Of Pfmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small endogenous RNAs that modulate gene‐expression post‐transcriptionally 14‐16 . Over the past decades, miRNAs have been confirmed to serve as important biomarkers for the treatment of renal diseases 17‐19 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] MicroRNAs (miRNAs) are small endogenous RNAs that modulate gene-expression post-transcriptionally. [14][15][16] Over the past decades, miRNAs have been confirmed to serve as important biomarkers for the treatment of renal diseases. [17][18][19] Importantly, it has reported that miRNAs are promising biomarkers for the diagnosis and prognosis of glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%